1997
DOI: 10.1159/000011839
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Load on the DNA Distribution Pattern of Bile Ductules and Cholangiocarcinoma Induced by Diisopropanolnitrosamine in Hamsters

Abstract: This study evaluated the influence of bile acid load on the DNA distribution pattern of proliferated bile ductules and cholangiocarcinoma induced by diisopropanolnitrosamine. Ninety hamsters were separated into control, tauro- and deoxycholic acid (DCA) groups. The DNA distribution pattern of intrahepatic lesions at 15–25 weeks was measured by cytofluorometry and classified into three types: I (-A, -B), II and III, according to the degree of dispersion on the DNA histogram. Regarding proliferated bile ductule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Conjugated bile acids have been described to be increased in CC patient serum [ 245 ], which might correlate with biliary tract tumorigenesis [ 246 , 247 ]. In human cholangiocyte cell lines, bile acids were shown to transactivate EGFR in a ligand-dependent manner via a TGF-α, which could be blocked by an MMP inhibitor [ 23 ].…”
Section: Egfr and Its Ligands In Hepatolithiasis And Cholangiocarmentioning
confidence: 99%
“…Conjugated bile acids have been described to be increased in CC patient serum [ 245 ], which might correlate with biliary tract tumorigenesis [ 246 , 247 ]. In human cholangiocyte cell lines, bile acids were shown to transactivate EGFR in a ligand-dependent manner via a TGF-α, which could be blocked by an MMP inhibitor [ 23 ].…”
Section: Egfr and Its Ligands In Hepatolithiasis And Cholangiocarmentioning
confidence: 99%
“…Secondary bile acids, such as deoxycholic acid and its conjugated forms, which have been reported to be increased in the serum of cholangiocarcinoma patients [83] , may be acting to promote cholangiocarcinogenesis in the biliary tract [20,84,85] through a mechanism involving bile acid-mediated activation of EGFR, leading to upregulation of COX-2 and protein turnover inhibition of the potent antiapoptotic protein, myeloid cell leukemia 1 (Mcl-1). Werneburg et al [26] have demonstrated that bile acids like deoxycholic acid can act to activate EGFR in cultured human H-69 cholangiocyte and KMBC cholangiocarcinoma cell lines by a TGF-α-dependent mechanism mediated by bile acid stimulation of matrix metalloproteinase activity catalyzing TGF-α membrane release.…”
Section: Bile Acidsmentioning
confidence: 99%
“…Bile acids, especially deoxycholic acid, promote an increase in nuclear DNA content or DNA polyploidization in cholangiocarcinoma and bile ductule lesions induced by diisopropanolnitrosamine in hamsters 15. With analysis of bile acid content in a choledochal cyst, Reveille et al14 proposed that unconjugated secondary bile acids (deoxycholate and chenodeoxycholate) may participate in the development of carcinoma.…”
Section: Pancreatic Juice Bile Acid Hyperplasia and Metaplasiamentioning
confidence: 99%
“…This mixture contains not only activated pancreatic enzymes but also certain mutagens 12,13. Changes in bile may induce chronic inflammation and increased cellular proliferation in the biliary tract mucosa, leading to epithelial hyperplasia, metaplasia, and carcinoma of the biliary system . Matsubara et al18 reported that inflammatory changes were found in all histologic specimens of noncancerous biliary epithelium in patients with APDJ, and 50% of these patients also showed hyperplasia and/or metaplasia.…”
Section: Pancreatic Juice Bile Acid Hyperplasia and Metaplasiamentioning
confidence: 99%